2003
DOI: 10.1046/j.1365-2222.2003.01584.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of immunoglobulin E synthesis and airway eosinophilia by vaccination with plasmid DNA encoding ProDer p 1

Abstract: These results suggest that vaccination with DNA encoding ProDer p 1 effectively fails to induce the allergen-induced IgE synthesis and airway cell infiltration. Plasmid DNA encoding ProDer p 1 may provide a novel approach for the treatment of house dust mite allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 51 publications
1
16
0
1
Order By: Relevance
“…Similar results have been demonstrated with DNA vaccines encoding allergens of house dust mite [12,19,20,21,22,23] and a DNA vaccine coding for the major milk allergen bovine β-lactoglobulin [24]. …”
Section: Th1-biased Immunity – the Key To Dna-based Allergy Vaccinationsupporting
confidence: 76%
See 3 more Smart Citations
“…Similar results have been demonstrated with DNA vaccines encoding allergens of house dust mite [12,19,20,21,22,23] and a DNA vaccine coding for the major milk allergen bovine β-lactoglobulin [24]. …”
Section: Th1-biased Immunity – the Key To Dna-based Allergy Vaccinationsupporting
confidence: 76%
“…It is characterized by airway obstruction, mucus hypersecretion and inflammation of the airways, including infiltration and activation of eosinophils in the bronchial mucosa. Several publications showed that DNA-based vaccines offer an intriguing long-term solution to counteract the early events in allergic inflammation of the lung [13,19,20,21, 23,25,26,27,28]. …”
Section: Th1-biased Immunity – the Key To Dna-based Allergy Vaccinationmentioning
confidence: 99%
See 2 more Smart Citations
“…In den darauf folgenden Jahren wurden DNA-Vakzine gegen eine Reihe von Modellmolekülen und klinisch relevanten Allergenen entwickelt [26][27][28][29][30][31][32]. Zu den diesbezüglich am besten untersuchten Allergenen gehört das Hauptallergen der Birkenpollen, Bet v 1, gegen das 1999 erstmals genetisch immunisiert wurde [17,[33][34][35][36].…”
Section: Erste Studien Zur Genetischen Immunisierung Gegen Allergieunclassified